Growing centralization in China's farmland protection policy in response to policy failure and related upward-extending unwillingness to protect farmland since 1978. (September 2017) - Zhong, Taiyang; Mitchell, Bruce; Scott, Steffanie; Huang, Xianjin; Li, Yi; Lu, Xiao
Since 1978, China has experienced a rapid loss of arable land, leading to centralizing of farmland protection policies. To understand the growing centralization, this paper has used the lens of the interactions among (1) unwillingness to protect farmland among diverse actors, (2) policy failure and (3) policy change. The growing centralization is an adaptive response to the unwillingness to protect farmland from local up to provincial government levels, and its associated policy failure. The article suggests that gradual centralization over the last almost 40 years has gone through three phases: centralization to county-level, centralization to provincial-level, and intensifying technical supervision from central government. In the first phase, the unwillingness to preserve farmland appeared at the levels of the rural household, village and township; in the second phase, county- and prefecture-level governments began to lose willingness to preserve farmland; and, in the third phase, provincial governments' willingness to preserve farmland weakened. The current centralized system has succeeded, for the most part, in addressing the problem of asymmetric information about farmland preservation between central and local governments, but the basic planning problem regarding loss of farmland remains a challenge.